Legal Status Of Forensic Biologist During Pre-Trial Investigation - Mosiiuk, Kateryna; Karasiova, Olga (Archives of Criminology and Forensic Sciences, 2022)
The current research paper studies and analyses the rights, duties, and prohibitive measures of a forensic biologist at the stage of pretrial investigation according to the current legislation of Ukraine. This research paper’s purpose is to reveal the legal status of forensic biologist during a pre-trial investigation of criminal proceedings. In criminal proceedings for murder, grievous bodily harm, rape, robbery, kidnapping, etc., traces of biological origin are significant physical evidence. One of the most effective ways to prevent such crimes is preventive activities of public administration entities, society, and ensuring the irreversibility of punishment of guilty people in the crime which is conducted with the participation of a forensic biologist, in most cases, after conducting a forensic examination.